Visual three-dimension finite-element analysis system (CPFEM) and its engineering application - SHEN Xiao-wen; WANG Fu-xi; QIAN Xiang-qun; SHI Wei (浙江大学学报. 农业与生命科学版, 2003)
The visual three-dimension finite-element analysis system (CPFEM) was developed, Which consisted of the modules with 15 nodes, 20 nodes, 8 nodes and 6 nodes respectively, a auto-dissecting module for some special parts (CPPIP), an interface module with SAP5M and ADINATM (CPCPP), and a post-processing module. The main functions of the system were introduced and several examples were given, which provided theoretical base for reliable design and improvement of machine structure.